Pemahaman Konsep Akuntansi Perusahaan Dagang Ditinjau Dari Persepsi Mahasiswa Tentang Cara Mengajar Dosen Dan Perilaku Belajar Mahasiswa Pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan Dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta - Elysia, Novita; , Drs. Sudarto MM (2016)
The purpose of this study is to determine contribution the effects of student's perceptions about the lecturer's teaching techniques and the effects of the student's learning behavior towards the comprehension of trading company's accounting concept in the Accounting department and teacher training and education faculty of University of Muhammadiyah Surakarta either partially or simultaneously. The type of this research is associative quantitative. The population in this study were the 2014 students' generation of accounting department of University of Muhammadiyah Surakarta, amounting to 211 students with a sample of 131 students were taken with proposional non random sampling technique. Data collection techniques using questionnaires that have been tested by validity and reliability testing. Technical analysis of the data used in this research is multiple regression, ttest, F-test, the effective contribution and relative contribution. The conclusion that can be drawn from this study are: 1) there is a significant relationship between students' perceptions about the lecturer's teaching techniques towards the comprehension of trading company's accounting concept based on t-test resulting thitung > ttabel , which is 2,620>1,984 and significant value < 0,05, which is 0,01. 2) there is a significant relationship between students' learning behavior towards the the comprehension of trading company's accounting concept based on t-test resulting thitung > ttabel, which is 3,384>1,984 and significant value < 0,05, which is 0,001. 3) There is a significant relationship between students' perceptions about the lecturer's teaching techniques and students' learning behavior towards towards the comprehension of trading company's accounting concept based on F-test resulting Fhitung>Ftabel 17,197>3,00 with significant value of 5%. The result of the calculation to the value of